The Influence of Lifestyle, Design and Price Perceived on Purchase Intention Yamaha NMAX Motorcycles in Tangerang City - Pamungkas, Galih; Hamdan Hamdan (Journal of Law, Politic and Humanities, 2021)
The purpose of this study was to determine the Analysis of Lifestyle, Design, and Price Perception of Interest in Buying a Yamaha NMAX Motorcycle in the City of Tengerang. The sample used in this study were 180 respondents with a quantitative method approach. The data collection method used is a questionnaire and using Accidental Sampling for sampling. This study uses SEM data analysis techniques and data processing using Partial Least Square (PLS). From the results of the study, it was found that Lifestyle, Design and Price Perception had a positive and significant effect on Purchase Interest of Yamaha NMAX Motorcycles.